2019
DOI: 10.14716/ijtech.v10i3.2905
|View full text |Cite
|
Sign up to set email alerts
|

Cellulase and Xylanase Immobilized on Chitosan Magnetic Particles for Application in Coconut Husk Hydrolysis

Abstract: Cellulase and xylanase were covalently immobilized on chitosan magnetic particles. They were employed as catalysts to produce reducing sugar from coconut husk individually and simultaneously. Fourier Transform Infrared Spectroscopy (FT-IR) and Bradford's protein analysis confirmed that the enzymes were covalently immobilized on the support. Cellulase from Aspergillus niger and Trichoderma reesei immobilized on chitosan magnetic microparticles yielded 0.352 g/L and 0.316 g/L of reducing sugar respectively, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…First, because it is necessary to coimmobilize the three enzyme families listed above, and second, due to the mechanism of action of cellulases, and the insoluble nature of cellulose, the initial activity of the immobilized biocatalyst is generally low. Several attempts were made for co-immobilization of cellulase components using a broad range of protocols and supports such CLEAs (Bhattacharya and Pletschke, 2014;Dal Magro et al, 2016;Jafari Khorshidi et al, 2016;Li et al, 2012;Periyasamy et al, 2016;Perwez et al, 2019), chitosan (Hamzah et al, 2019;Mandal, 2019;Masoumeh Mohammadi et al, 2019), non-porous materials (as all enzyme is on the surface of the support, they should be able to attack even insoluble substrates) such as magnetic nanoparticles (Ariaeenejad et al, 2020;Asar et al, 2019;Dal Magro et al, 2018;Giannakopoulou et al, 2019;Muley et al, 2020Muley et al, , 2018Raza et al, 2019) and carbon nanotubes (Abraham and Puri, 2020;Li et al, 2019a;Papadopoulou et al, 2019;Raza et al, 2019;Sillu and Agnihotri, 2020), and others. In some cases, some exogenous β-glucosidase is added to the cellulase components mixture to avoid the inhibition caused by cellobiose in some of the cocktails components.…”
Section: Hydrolysis Of Polysaccharidesmentioning
confidence: 99%
“…First, because it is necessary to coimmobilize the three enzyme families listed above, and second, due to the mechanism of action of cellulases, and the insoluble nature of cellulose, the initial activity of the immobilized biocatalyst is generally low. Several attempts were made for co-immobilization of cellulase components using a broad range of protocols and supports such CLEAs (Bhattacharya and Pletschke, 2014;Dal Magro et al, 2016;Jafari Khorshidi et al, 2016;Li et al, 2012;Periyasamy et al, 2016;Perwez et al, 2019), chitosan (Hamzah et al, 2019;Mandal, 2019;Masoumeh Mohammadi et al, 2019), non-porous materials (as all enzyme is on the surface of the support, they should be able to attack even insoluble substrates) such as magnetic nanoparticles (Ariaeenejad et al, 2020;Asar et al, 2019;Dal Magro et al, 2018;Giannakopoulou et al, 2019;Muley et al, 2020Muley et al, , 2018Raza et al, 2019) and carbon nanotubes (Abraham and Puri, 2020;Li et al, 2019a;Papadopoulou et al, 2019;Raza et al, 2019;Sillu and Agnihotri, 2020), and others. In some cases, some exogenous β-glucosidase is added to the cellulase components mixture to avoid the inhibition caused by cellobiose in some of the cocktails components.…”
Section: Hydrolysis Of Polysaccharidesmentioning
confidence: 99%
“…As previously studied, FT-IR spectra that indicated enzymes immobilized on CMNP had been investigated. The significant change of peak was found at 3267.54 cm -1 (N-H); 1629.15 cm -1 (C=O); 1027.66 cm -1 (C-N), and 1376.0 cm -1 (C-O) wavelength [14,15]. The illustration of the mechanism of immobilization is shown in figure 2.…”
Section: Enzyme Immobilization On Cmnp and Thermal Stabilitymentioning
confidence: 96%
“…Previous studies have also confirmed that bioenzymes can be immobilized with magnetic chitosan. The ability to undergo covalent binding produced strong enzyme activity and immobilization was confirmed by characterization of the sample with FTIR (Hamzah et al, 2019).…”
Section: Introductionmentioning
confidence: 93%